2007
DOI: 10.1007/s00128-007-9246-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Copper, Zinc, Chromium, Lead and Cadmium Levels in Hepatopancreas, Gill and Muscle Tissues of the Mussel Brachidontes pharaonis Fischer, Collected along the Mersin Coast, Turkey

Abstract: Levels of copper, zinc, cadmium, chromium and lead were determined in the gill, hepatopancreas and muscle tissues of Brachidontes pharaonis collected from the Mersin coasts of Turkey. Water and animal samples were collected monthly from the four stations between June 2002 and May 2003 for metal determinations. Metal levels in water samples of Mersin coasts were higher than those measured in other parts of Turkish coasts. Levels of metals in soft tissues of B. pharaonis showed an increase towards autumn and win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Concentrations of Cu and Cd were varied significantly in different seasons ( P < 0.05). The significant differences found in the mineral contents may be partly due to the seasonal variation in the metabolic activity of mussels and chemical properties of seawater , . During the whole study period, the contents of Pb (0.14−0.18 mg/kg WW) and Cd (0.25−0.48 mg/kg WW) in thick shell mussels were well below the maximum limits (1.5 mg/kg WW for Pb and 1 mg/kg WW for Cd) set by European Union .…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Concentrations of Cu and Cd were varied significantly in different seasons ( P < 0.05). The significant differences found in the mineral contents may be partly due to the seasonal variation in the metabolic activity of mussels and chemical properties of seawater , . During the whole study period, the contents of Pb (0.14−0.18 mg/kg WW) and Cd (0.25−0.48 mg/kg WW) in thick shell mussels were well below the maximum limits (1.5 mg/kg WW for Pb and 1 mg/kg WW for Cd) set by European Union .…”
Section: Resultsmentioning
confidence: 83%
“…Concentrations of Cu and Cd were varied significantly in different seasons (P < 0.05). The significant differences found in the mineral contents may be partly due to the seasonal variation in the metabolic activity of mussels and chemical properties of seawater (16,27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes of element content may take place because of metabolic activities due to the season and seasonal differences in the chemical properties of sea water (Karayakar et al, 2007); studies of Astorga-Espana et al (2007) and Li et al (2010) showed that lead (0.14-0.18 mg/kg) and cadmium (0.25-0.48 mg/kg) content of the thickshelled mussels were below the maximum limits of European Union (1.5 mg/kg for lead; 1 mg/kg for cadmium) and Cr (0.13-0.19 mg/kg) and Cu (1.3-3.8 mg/kg) were below the maximum limits too. Lead and Cd concentration of Mytilus edulis was 162 and 0.82 mg/kg respectively (Olafsson, 1986), 21 and 4 mg/kg in Mytilus galloprovincialis in Çam Bay of East Black Sea (Cevik et al, 2008) and 15.7, and 0.168 mg/kg in Mytilus chilensis (Astorga-Espana et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The intertidal mussel Brachidontes pharaonis from the family Mytilidae is present in the coasts of the western Pacific Ocean, Indian Ocean, Red Sea, and Mediterranean Sea (Taylor, 1971;Sasekumar, 1974;Barash and Danin, 1986;Morton, 1988). Several studies have demonstrated the metal bio-accumulation capacity of B. pharaonis at polluted and pristine locations along the coasts of the Mediterranean Sea (Göksu et al, 2005;Karayakar et al, 2007;Dar et al, 2018;Hamed et al, 2020). However, to the best of our knowledge, none has presented the depuration dynamics of this species.…”
Section: Introductionmentioning
confidence: 99%